Regulasi Dan Upaya Penyuluh Agama Islam: Literasi Sebagai Landasan Sosial-Keagamaan Di Era Digital - Jerry Hendrajaya; Ekawati Ekawati; Ahmad Irfan Mufid; Umi Kulsum; Mulyawan Safwandy Nugraha; Gustin Gustin (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2022)
The problem of religious counselor has the same problem as their equivalent, namely that the existence of these instructors almost does not get the support of great attention both in terms of regulation and understanding of literacy as a socio-religious foundation in the digital era. The purpose of this research is to study the strengthening of regulations and literacy efforts as a socio-religious foundation for religious counselors in the digital era. The research methodology is qualitative with a socio-legal research approach. Through a study of regulations and efforts of Islamic religious counselors: Literacy as a socio-religious foundation in the digital era, concluded that: 1) In terms of regulations required by the technical implementation of the functional implementation of Religious Extension Officers for Permanpan RB No. 9 of 2021 and the formulation of 19 derivatives of the Permanpan as the task of the Ministry of Religion of the Republic of Indonesia as the agency for fostering Religious Extension; and 2) Efforts to improve the quality of literacy as a socio-religious foundation for Islamic religious counselors in the digital era by providing continuous training rooms in the use of technology, information and communication tools, thematic training programs on religious content for extension social media users, program implementation socio-religious studies funded by the relevant government for religious counselors and the implementation of skills in writing scientific papers on socio-religious in a comprehensive manner on an ongoing basis.